The norms of Minnesota multi faces personality inventory (second edition) MMPI-2 and the sixteen personality factor questionnaire of catel (fifth edition) (Journal Of Educational and Psychological Researches, 2018)
The aim of the current study is to create special norms of the second edition of Minnesota multi faces personality inventory, and the fifth edition of the sixteen personality factor questionnaire of catel. To this end, the researcher applied the Minnesota multi faces personality inventory over a sample of (1646) secondary and university students as well as plenty of disorders. She also applied the sixteen personality factor questionnaire of catel on (4700) secondary and university students. SPSS tools were used to process data.